REPRESENTASI PELECAHAN SEKSUAL PADA FILM PROMISING YOUNG WOMAN: Analisis Semiotika Roland Barthes - Jody Kurnia Alviansyah (2023)
The aim of this research is to describe the depiction of sexual harassment in the film Promising Young Woman by director Emerald Fennell. The research data were analyzed using Roland Barthes' semiotic analysis technique which used a two-stage signification model, namely denotation, connotation, and myth. The film Promissing Young Woman itself tells the story of sexual harassment against women which ends in revenge. Cassie (Carey Mulligan), a 39 year old woman who works as a waitress in a coffee shop. Once a medical student, Cassie decided to quit and no longer continue her education after the tragedy that befell her best friend. In this study the approach used was descriptive qualitative with data obtained through observation of film scenes. The results of this study prove that the representation of sexual depictions found in the film Promising Young Woman is evidenced by the presence of signs of sexual harassment values contained in several scenes, whether visualized in pictures or dialogues.